Analysis Of Dispute Resolution With Arbitration Measures Based On Law N0. 30 Year 1999 - Ahmad Muharrom; David kurniawan; Dede Kurniawan; Mhd anggi Hermawan; Reza Sahputra Panyalai (ISNU Sumatera Utara, 2024)
Dispute resolution is one of the important aspects in various legal relationships, whether in the field of business, contracts, or personal relationships. Law No. 30/1999 on Arbitration and Alternative Dispute Resolution provides a clear legal framework for resolving disputes through arbitration. Arbitration offers various advantages such as a fast and cost-effective process, binding results, so that it is increasingly in demand as an alternative to dispute resolution compared to litigation in court. This analysis aims to explore and explain the steps of dispute resolution through arbitration starting from the submission of a request for arbitration, the appointment of arbitrators, to the enforcement of arbitral awards. By understanding these steps, it is expected that the parties involved in the dispute can make a better decision on the appropriate settlement method.